Dinamika Ekonomi dan Politik dalam Pusaran Korupsi Indonesia - Geronsius Arinto Guru; Hartanto Hartanto; Murdomo Murdomo (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2025)
Corruption is a major challenge, especially in developing countries, which has a significant impact on the economy and politics. In Indonesia, this corruption problem has long occurred with one of the important points being the establishment of the Corruption Eradication Commission, and currently the independence of the Corruption Eradication Commission is actually decreasing. This article draws one formulation of the problem, namely how are the dynamics of the economy and politics in the grip of corruption in Indonesia? Through empirical research methods and theoretical approaches. The results of this analysis indicate that corruption has a very negative impact on the Indonesian economy and politics, damaging the economic structure, exacerbating social inequality, and weakening democracy and public trust. To overcome this, laws such as the Corruption Eradication Law, the State Finance Law, and the Election Law are important in creating a transparent and accountable government. Strengthening the mechanism for preventing and eradicating corruption is concluded to be able to improve economic and political conditions, as well as provide greater benefits to society. ___ Referensi Books with an author: Klitgaard, R. (1988). Controlling Corruption, California: University of California Press. Marzuki, P. M. (2016). Penelitian Hukum, Jakarta: Kencana. Rose-Ackerman, S., & Palifka, B. J. (2016). Corruption and government: Causes, consequences, and reform. Cambridge: Cambridge University Press. Journal articles: Adiguna, R. S. (2024). Resilient Indonesia Melangkah Tegar Menghadapi Krisis Moneter dan Membangun Kembali Perekonomian 1997–2000an. Jurnal Senja Sejarah dan Sosial Humaniora, 2(2). https://doi.org/10.36761/jssh.v2i2.4300 Astuti, T., Purwanda, S., Prasisto, J., & Prayudi, P. (2024). PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PEREDARAN OBAT TANPA IZIN EDAR:(Studi Putusan Nomor 1/Pid. Sus/2023/Pn. Pre). Jurnal Hukum Positum, 9(1), 1-16. https://journal.unsika.ac.id/positum/article/view/11132 Cahyadi, J. (2025). Peran Media Sosial dalam Pengawasan dan Pencegahan Korupsi di Indonesia. Journal of Management and Creative Business, 3(1), 190-198. https://doi.org/10.30640/jmcbus.v3i1.3561 Cintana, D., Haidillah, A. S., Zulfa, S. A., Muhadi, A. A., & Khodijah, S. (2025). Dampak Korupsi bagi Pembangunan Ekonomi Nasional. Journal of the Research Center for Digital Democracy, 1(1), 12-18. https://journal.idede.org/index.php/IDEDE/article/view/137 Dewi, M. N. K., Miqat, N., & Purwanda, S. (2024). Analysis of the Legal Substance of Indonesia's Bilateral Investment Treaty (BIT): Balance of Rights and Obligations Based on National Interest. Pena Justisia: Media Komunikasi dan Kajian Hukum, 23(3), 3216-3232. https://doi.org/10.31941/pj.v23i3.5619 Fadhil, M. (2019). Komisi Pemberantasan Korupsi, politik hukum antikorupsi dan delegitimasi pemberantasan korupsi. Al Ahkam, 15(2), 7-36. https://jurnal.uinbanten.ac.id/index.php/ahkm/article/view/2203 Farida, F., Rasda, D., & Mutmainna, M. (2023). Implikasi Media Sosial Dalam Tahapan Kampanye Pemilu Serentak Tahun 2024. Vifada Assumption Journal of Law, 1(2), 30-37. https://doi.org/10.70184/gmt7gs45 Hariyanto, M. (2019). Perspektif inflasi dalam ekonomi Islam. Al-Mizan: Jurnal Ekonomi Syariah, 2(2), 79-95. https://ejournal.an-nadwah.ac.id/index.php/almizan/article/view/112 Hartanto, H., Chrisjanto, E., & Murdomo, M. (2024). Korupsi dan Pengaruh Kekuasaan Partai Politik (Follow The Money and Asset Recovery). Iqtisad: Reconstruction of Justice and Welfare for Indonesia, 11(1), 57-78. https://doi.org/10.31942/iq.v11i1.10910 Hermawan, D., Fatullah, A. P., Cayadi, C., Hidayat, A., & Jainah, Z. O. (2024). Analisis Dampak Korupsi Dalam Pembangunan Infrastruktur Di Negara Berkembang. Innovative: Journal Of Social Science Research, 4(1), 4259-4271. https://j-innovative.org/index.php/Innovative/article/view/7045 Indrawan, R. M. J., & Widiyanto, B. (2017). Korupsi sebagai bagian dari perang proxy: upaya untuk memberantas bahaya korupsi di Indonesia (Corruption as part of proxy war: effort to eradicate the danger of corruption in Indonesia). Jurnal Pertahanan dan Bela Negara, 7(1), 21-38. https://doi.org/10.33172/jpbh.v7i1.128